Sex-based differences in bacterial meningitis in adults: Epidemiology, clinical features, and therapeutic outcomes - Dong-Y. Hsieh; Yun-R. Lai; Chia-Y. Lien; Wen-N. Chang; Chih-C. Huang; Ben-C. Cheng; Chia-T. Kung; Cheng-H. Lu (Elsevier, 2021)
Background: To investigate the sex-based differences in clinical features, causative pathogens, and outcomes of hospital-based culture-proven adult bacterial meningitis. Objective: This retrospective study enrolled 621 patients at a tertiary medical center. To compare changes over time, the presentation of disease among the enrolled patients was divided into two equal time periods: the first study period (1986-2002) and the second study period (2003-2019). Results: Of the 621 patients enrolled in this study, 396 were males and 225 were females. The overall case fatality rate was 30.4% with 30.1% and 31.1% in males and females, respectively. Regarding the causative pathogens, there was a rising incidence of coagulase-negative staphylococcal infections and a decreasing incidence of Klebsiella pneumoniae infection in both male and female in the second study period. The prevalence of patients with nosocomial infection in a postneurosurgical state were 41.9% (68/162) in the first study period and 58.1% (94/162) in the second study period in male group, and 34.8% (32/92) in the first study period and 65.2% (60/92) in the second study period in female group, respectively. Significant factors between the sexes difference included age (P = 0.004), traumatic brain injury (P = 0.01), alcoholism (P < 0.001), brain tumor (P < 0.001), systemic lupus erythematosus (SLE) (P = 0.004), presence of diabetic ketoacidosis/hyperglycemic hyperosmolar state (P = 0.033), brain abscess (P = 0.042), and total protein (P = 0.002) and white blood cell count (P = 0.036) of cerebrospinal fluid data. Conclusion: Our study revealed an increase in the number of patients with nosocomial infection with a postneurosurgical state in both male and female in the second study period. Males were younger and frequently presented with a history of head trauma and alcoholism with concomitant brain abscesses while females presented with SLE and brain tumor. The therapeutic outcome did not show differences between the sexes.